1984
DOI: 10.2113/gsecongeo.79.5.848
|View full text |Cite
|
Sign up to set email alerts
|

The Logtung large tonnage, low-grade W (scheelite)-Mo porphyry deposit, south-central Yukon Territory

Abstract: The Logtung deposit, discovered in 1976, is an example of large tonnage (162 million metric tons), low-grade (0.13% WO3 and 0.052% MoS2) W(scheelite)-Mo mineralization related to multiple felsic intrusions. Since mineralization is contained in fractures ()95%) rather than being disseminated Logtung is not a skarn deposit. The principal reason is that the quartz-diopside-garnet calc-silicate, biotite-quartzite, and wollastonite-vesuvianite calcsilicate reaction skarn host rocks to mineralization, which were der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 10 publications
1
19
0
Order By: Relevance
“…Scheelite (-molybdenite) stockworks. The recent work of Noble et al (1984) has clarified the nature of the Logtung W-Mo deposit, southern Yukon, and has demonstrated that scheelite-rich stockwork, or porphyry, deposits may constitute significant concentrations of tungsten. This is also apparent from Yan et al's (1980) description of the Yanchuling W-Mo deposit, southern China.…”
Section: Comparison With Other W(-mo) Depositsmentioning
confidence: 99%
See 3 more Smart Citations
“…Scheelite (-molybdenite) stockworks. The recent work of Noble et al (1984) has clarified the nature of the Logtung W-Mo deposit, southern Yukon, and has demonstrated that scheelite-rich stockwork, or porphyry, deposits may constitute significant concentrations of tungsten. This is also apparent from Yan et al's (1980) description of the Yanchuling W-Mo deposit, southern China.…”
Section: Comparison With Other W(-mo) Depositsmentioning
confidence: 99%
“…Features shared by Lake George and Logtung (Noble et al, 1984) include: (1) the association with epizonal stocks of biotite (-hornblende) monzogranite, with A/CNK 2: 1, and with porphyritic felsic dikes; (2) the mixed calcareous-noncalcareous nature of the metapelitic country rocks which host the bulk ofthe stockwork mineralization; (3) the premineralization development of calc-silicate hornfels, in part through bimetasomatic reactions during metamorphism; (4) the absence of pervasive hydrothermal alteration; (5) the occurrence of several stages of W-and/or Mobearing veinlets; (6) the emplacement of porphyry dikes between the first and second stage of mineralization; (7) the association of calc-silicate minerals with the earliest mineralization; (8) the lack of a systematic W vs. Mo zonation relative to the center; and (9) the association with late-stage, base metal sulfide veins, containing, among others, sphalerite, galena, arsenopyrite, and bismuthinite. This stage is apparently better developed at Logtung, unless the major Sb veins at Lake George are representative of such mineralization.…”
Section: Comparison With Other W(-mo) Depositsmentioning
confidence: 99%
See 2 more Smart Citations
“…For this reason the Tungsten Suite is considered the most likely to contain tungsten skarn and associated ore in the study area (Rasmussen et al 2007). The intrusion-related skarn deposits in the MSM area are coeval with other Cretaceous examples in the Cordillera, such as the Scheelite Dome deposit in the Yukon (Mair et al 2006b), and the Northern Dancer/Logtung deposit in southern Yukon and northern British Columbia (Noble et al 1984(Noble et al , 1986. Possible North American correlatives to Cantung and Mactung include tungsten skarn deposits associated with ca.…”
Section: Intrusion-related Skarn Depositsmentioning
confidence: 97%